2014
DOI: 10.1007/s00059-013-4040-7
|View full text |Cite
|
Sign up to set email alerts
|

Sozioökonomischer Status und inflammatorische Biomarker für Herz-Kreislauf-Erkrankungen

Abstract: The SES gradient in cardiovascular diseases reflects behavioral as well as physiological pathways and systemic inflammation seems to be involved. Low SES is associated with an increased exposure to adverse circumstances of life, which can trigger biological responses and result in an increased risk of cardiovascular diseases. Medical history taking in cardiology should focus on socio-structural exposures and thereby reflect the different meanings of education, occupation and income.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 70 publications
2
4
0
Order By: Relevance
“…Thus, we cannot assign a particular inflammation inducing effect to abdominal fat, but to obesity (iii) in general accounting for a maximum of just fewer than 50% on the total educational differences in inflammation. Previous research confirmed a higher awareness to health issues and wider acceptance of scientific findings related to disease prevention and lifestyle in people with higher education (32). Although our cohort consisted of older subjects, the educational level appears to be a stable factor influencing health conviction and health status over several decades.…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations
“…Thus, we cannot assign a particular inflammation inducing effect to abdominal fat, but to obesity (iii) in general accounting for a maximum of just fewer than 50% on the total educational differences in inflammation. Previous research confirmed a higher awareness to health issues and wider acceptance of scientific findings related to disease prevention and lifestyle in people with higher education (32). Although our cohort consisted of older subjects, the educational level appears to be a stable factor influencing health conviction and health status over several decades.…”
Section: Discussionsupporting
confidence: 66%
“…Previous research confirmed a higher awareness to health issues and wider acceptance of scientific findings related to disease prevention and lifestyle in people with higher education . Although our cohort consisted of older subjects, the educational level appears to be a stable factor influencing health conviction and health status over several decades.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…It also requires that paediatrics and medical sociology are reciprocally more aware of the literature in order to further develop joint frameworks and conceptual models as well as measurements and research designs. Another task of such a biopsychosocial as well as explicitly social research on adolescent health would be to focus on the question how social influences are embodied in physiological characteristics and thus exert an influence on health as well as how they are reflected in social inequalities in health [29,38,64]. This would provide new insights on how social conditions form a) the expression of biological features and b) societal patterns of health and disease.…”
Section: Challenges In Basic Research On Adolescent Healthmentioning
confidence: 99%